Detection of microRNA in urine to identify patients with endometrial cancer: a feasibility study. Issue 6 (June 2021) - Donkers, Hannah; Hirschfeld, Marc; Weiß, Daniela; Erbes, Thalia; Jäger, Markus; Pijnenborg, Johanna; Bekkers, Ruud; Galaal, Khadra
ABSTRACT : Objective : To find dysregulated urinary microRNAs associated with endometrial cancer as a first step in finding a non‐invasive new diagnostic biomarker. The second objective is to determine the correlation of urinary microRNAs with clinicopathological characteristics. Methods : A prospective cohort study of patients presenting with abnormal bleeding between March and November 2019 was performed at the Royal Cornwall Hospital Trust Truro. Urine samples were obtained from women diagnosed with endometrial cancer and benign endometrial sampling. MicroRNA was isolated and quantitative real time PCR was used to detect expression levels of microRNAs. Results : A total of 61 women were included in this study: 24 endometrial cancer patients, and 37 controls. Median age was 64 years (range 45‐94) and median body mass index was 29 kg/m 2 (range 17‐54). MiR‐223 was significantly up‐regulated in urine of endometrial cancers patients (p=0.003). Furthermore, let7‐i, miR‐34a, and miR‐200c were significantly down‐regulated and miR‐424 was up‐regulated in obese women. In addition, miR‐148a and miR‐222 were significantly down‐regulated in elderly women, and miR‐16, miR‐26b, and miR‐200c were significantly deregulated in women with multiple comorbidities. Conclusion : MicroRNA expression levels in urine can potentially be used as a non‐invasive diagnostic test for endometrial cancer. Furthermore, aberrant microRNA expression in urine is associated with patient characteristics. Further research in larger trials is needed to validate the potential utility of urinary microRNAs.